Humans and non-humans in the Radio Ucamara videos of the Kukama Kukamiria indigenous people (Peru): an approach from neomaterialism - Angulo-Giraldo, Miguel (2022)
For the Kukama Kukamiria indigenous people (Peru), a diversity of agents (human and non-human) are constantly interrelated through a large network in which the different intertwines allow associative communication (contrary to social communication). From the theoretical proposal of neomaterialism (Lemos, 2013; Lemos, 2020) and the actor-network (Latour, 2005; Latour, 2012), this relational coexistence is studied through the videos produced by Radio Ucamara, owned and directed by members of the Kukama Kukamiria indigenous people. From a qualitative, cross-sectional, observational-descriptive analysis, indigenous communication processes are studied from four songs (Parana, Omagua, Aparecimos and Kamatia) that appeared on the YouTube platform of Radio Ucamara between 2015 and 2019. Emphasis is placed on the modes of existence, agencies (human and non-human) and radical mediations. The study concludes that, based on the applied theory, it is in the mediations themselves (the interlacing and associations between different agents) that materiality (agencies) is produced, which shape an associative communication.